IJCM_188A: Exploring Factors Influencing Medication Non-Adherence Among Urban Residents with Non-Communicable Diseases in Chengalpattu District: A Descriptive Cross-Sectional Study - Yuvashree T.; Venkatesan Murugan (Wolters Kluwer Medknow Publications, 2024)
Background: Medication non-adherence is a modifiable risk factor for non-communicable diseases (NCDs). WHO estimated the average rate of medication adherence to be around 50% in developed countries and to be lower in the developing countries. Objectives: To find the factors influencing medication non-adherence among patients diagnosed with NCDs in the urban areas. Methodology: A cross sectional study was conducted among 200 patients visiting Urban Health Training Centre, MAPIMS. A structured questionnaire was used to collect data on socio-demographic characteristics, risk factors, self-care practices, access to health care and family support to medication adherence. The outcome of the study was medication adherence measured using the eight-item Morisky medication adherence scale (MMAS-8). Results: Among the 200 participants with one or more non-communicable diseases (NCDs), the result found the prevalence of poor medication adherence rate to be 53.5%. Poor medication adherence was more prevalent in the older age group (39%, n=78), female patients (57.5%, n=115), with primary education (49.5%, n=99), unemployed individuals (58.5%, n=117), those without regular physical activities (63.5%, n=127) and classified as obese (43%, n=86). Conclusion: The study concluded that the prevalence of poor medication adherence was more common among NCD patients and the need to develop effective strategies to enhance medication adherence according to patient's requirements through a holistic approach, by strengthening the primary health care system to achieve better health outcomes.